2009
DOI: 10.1002/ppul.21066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active smoking on asthma symptoms, pulmonary function, and BHR in adolescents

Abstract: Current smoking was significantly associated with symptoms of asthma, such as having recent wheezing and recent exercise-induced wheezing, especially for non-atopics, in Korean adolescent population. Current smoking was further associated with lower pulmonary function, but not BHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…Our results are in accordance with the two previous studies on nasal obstruction analyzed by acoustic rhinometry [5,6] and a recently published study [21] reporting a reduced mucosal decongestion in smokers. Signs of lower airway obstruction were found in adolescents with active smoking habits [22][23][24][25], which also is in agreement with our findings. Our study indicates that the very low exposure dose in adolescent smokers with occasional habits may result in a functional disorder with a reduced plasticity of the airways.…”
Section: Discussionsupporting
confidence: 95%
“…Our results are in accordance with the two previous studies on nasal obstruction analyzed by acoustic rhinometry [5,6] and a recently published study [21] reporting a reduced mucosal decongestion in smokers. Signs of lower airway obstruction were found in adolescents with active smoking habits [22][23][24][25], which also is in agreement with our findings. Our study indicates that the very low exposure dose in adolescent smokers with occasional habits may result in a functional disorder with a reduced plasticity of the airways.…”
Section: Discussionsupporting
confidence: 95%
“…These included maternal smoking during pregnancy [23] or during the 1 st year of life [24], mother smoking in general [19], and heavily smoking parents (67% among non-atopic asthmatics vs 40% among non-asthmatics) [44]. Active smoking by the adolescent was identified as a significant risk in two studies [45,46]. Inconsistent results were reported for second-hand smoking: one study estimated a risk [23], whereas another one reported no effect [38].…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents with asthma are expected to avoid smoking because it might initiate or aggravate asthmatic symptoms [6]. Further, asthmatics who smoke have more asthma attacks, worse pulmonary function and higher rates of hospitalization [7].…”
Section: Introductionmentioning
confidence: 99%